Rancang bangun mesin planetary ball mill type vertikal skala laboratorium dengan variasi kecepatan putaran - Pancarana, I Dewa Made; Waisnawa, I Gede Nyoman Suta; Firdaus, Muhammad Nabil (Fakultas Teknik UMSU, 2024)
This paper discusses the design and manufacture of a laboratory-scale vertical planetary ball mill machine with variations in rotational speed. The purpose of making this planetary ball mill machine is to support the completeness of equipment in the laboratory at the Department of Mechanical Engineering, Bali State Polytechnic.This vertical type planetary ball mill machine has dimensions of 300 x 300 x 550 mm and two stainless steel stirring tubes with a capacity of 500 ml each. The engine frame is made of hollow galvanized iron measuring 3 x 3 cm. This vertical type planetary ball mill machine is driven by an AC 125 watt 220 volt 2800 rpm electric motor. The transmission system uses one straight gear (driving gear) and two straight gears (driven gear). The driving gear is mounted on the motor shaft, while the driven gear is attached to each stirrer tube. To adjust the amount of rotation, a 2000 W/220 V AC motor dimmer is used. Tests on the vertical planetary ball mill machine were carried out 8 times using 200 grams of wheat flour and 50 grams of water (4:1) for each experiment. Four times the experiments were carried out at rotational speeds of 250, 500, 750, and 1000 rpm for 5 minutes each and four times the experiments were carried out at rotational speeds of 250, 500, 750, and 1000 rpm for 10 minutes each. The test results show that a homogeneous mixture occurs faster with increasing rotations with a fixed time or lengthening the rotation time in each round.